Pengaruh Media Sosial, Pendidikan Kewirausahaan, Ekspektasi Pendapatan Dan Religiusitas Terhadap Minat Bisnis - Rahmat Jumadi; Nur Huri Mustofa (Al Maal: Journal of Islamic Economics and Banking, 2022)
This study aims to determine the using social media, entrepreneurship education, income expectations, and religiosity on business interests. This research is a type of quantitative research and the data used are primary data. The populatioin in this study were students of the islamic Economics and Business Faculty, Salatiga State Islamic Institute with the criteria that they had taken entrepreneurship courses. The number of samples in this study were 93 students with a proportional stratified random sampling technique. The methid of data collection is through the distribution of questionnaires which are then analyzed by multiple linier regression. The resut of this study are the social media and entrepreneurship education has no effect on business interest, while income expectations and religiosity affect business interest.